Islamic business coaching from the perspective of Indonesian coaches - Sholahuddin, Muhammad; Abdullah, Moha Asri; Barom, Mohd Nizam; Tahir, Ibrahim Nuhu (Global Academic Excellence, 2019)
In an increasingly competitive era of trade, training is insufficient to help solve business problems and challenges that often change daily. Meanwhile, business professionals realize that the coaching process used for the past dozen years by athletes, orators, and artists to improve their performance can also be used to help entrepreneurs to help accelerate business goals and personal success. Organizations that offer coaching have grown rapidly over the past decade. Even though in Indonesia, several coaching Islamic businesses have their communities, until now there is limited literature on Islamic business coaching. This study develops definitions for Islamic business coaching along with its characteristics for the Indonesian setting. This was achieved using qualitative research. Data were collected with interviewing 5 Islamic Indonesian master coaches. Recording of interviews was transcribed and coded. Then, those were analyzed with content analysis. The paper concludes that Islamic business coaching differs from conventional coaching due to being based on Islamic religiosity and principles. In Addition, the characteristics of Islamic business coaching include Islamic business coach’s role, Islamic business coaching session focus, and Islamic business coaching results.